DnaB proteolysis in vivo regulates oligomerization and its localization at oriC in Bacillus subtilis - Grainger, William H.; Machón, Cristina; Scott, David J.; Soultanas, Panos (Oxford Journals, 2010)
Initiation of bacterial DNA replication at oriC is mediated by primosomal proteins that act cooperatively to melt an AT-rich region where the replicative helicase is loaded prior to the assembly of the replication fork. In Bacillus subtilis, the dnaD, dnaB and dnaI genes are essential for initiation of DNA replication. We established that their mRNAs are maintained in fast growing asynchronous cultures. DnaB is truncated at its C-terminus in a growth phase-dependent manner. Proteolysis is confined to cytosolic, not to membrane-associated DnaB, and affects oligomerization. Truncated DnaB is depleted at the oriC relative to the native protein. We propose that DNA-induced oligomerization is essential for its action at oriC and proteolysis regulates its localization at oriC. We show that DnaB has two separate ssDNA-binding sites one located within residues 1-300 and another between residues 365-428, and a dsDNA-binding site within residues 365-428. Tetramerization of DnaB is mediated within residues 1-300, and DNA-dependent oligomerization within residues 365-428. Finally, we show that association of DnaB with the oriC is asymmetric and extensive. It encompasses an area from the middle of dnaA to the end of yaaA that includes the AT-rich region melted during the initiation stage of DNA replication.